A Application of Contextual Teaching and Learning (CTL) Model Learning with Reality Media to increase Creativity and Science Learning Outcomes: with Reality Media to increase Creativity and Science Learning Outcomes - Indah Safitri; Ririn Andriani Kumala Dewi (Jurnal Pendidikan dan Pengajaran, 2023)
Based on the results of observations, it was found that there was low creativity and learning outcomes for class III MI Hidayatul Islamiyah Jagapura Kulon in science subjects, namely 61.35%, still below the KKM. The low creativity and student learning outcomes are caused by the lack of media/visual aids and the management of learning by the teacher is less than optimal. This study uses Classroom Action Research (CAR), which consists of four components, namely planning, action, observation and reflection. Based on the results of the data obtained from the observations of cycle I with a percentage of 72% (good enough), cycle II with a percentage of 81% (good) and cycle III with a percentage of 92% (very good). The classical student questionnaire results from cycle I with a percentage of 70.43% (moderate creativity) increased in cycle II with a percentage of 86.13% (high creativity) and improved very well in cycle III with a percentage of 90.08% (high creativity). Student learning outcomes in cycle I got an average score of 56 and a complete percentage of 43% increased in cycle II with an average score of 77 and a complete percentage of 88% increased very well in cycle III of 96%. Thus the application of the CTL model can increase creativity and science learning outcomes on human growth and development in class III MI Hidayatul Islamiyah students for the 2021/2022 academic year.